2012
DOI: 10.2106/jbjs.k.00467
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Anterior Cruciate Ligament Injury Prevention Training Programs

Abstract: Our study indicated strong evidence in support of a significant effect of ACL injury prevention programs. Our pooled estimates suggest a substantial beneficial effect of ACL injury prevention programs, with a risk reduction of 52% in the female athletes and 85% in the male athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
141
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(149 citation statements)
references
References 44 publications
3
141
0
5
Order By: Relevance
“…They are easy to perform, are inexpensive, and take approximately 15 to 20 minutes to complete per session, and the evidence supporting their benefits is growing. 20,23 However, fewer than half of the participants in our study reported performing specific exercises to reduce this risk. When considering the results of DiStefano et al 20 that athletes who displayed the greatest LESS scores improved the most after an ACL injuryprevention program and considering that our study revealed most female adolescent athletes demonstrated poor mechanics, we recommend that all female adolescent athletes within youth sport participation receive injury-prevention training, regardless of whether they are SSS or M-S athletes.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…They are easy to perform, are inexpensive, and take approximately 15 to 20 minutes to complete per session, and the evidence supporting their benefits is growing. 20,23 However, fewer than half of the participants in our study reported performing specific exercises to reduce this risk. When considering the results of DiStefano et al 20 that athletes who displayed the greatest LESS scores improved the most after an ACL injuryprevention program and considering that our study revealed most female adolescent athletes demonstrated poor mechanics, we recommend that all female adolescent athletes within youth sport participation receive injury-prevention training, regardless of whether they are SSS or M-S athletes.…”
Section: Discussionmentioning
confidence: 74%
“…This finding highlights the need for greater implementation of programs, such as the Prevent Injury and Enhance Performance (PEP) and Sportsmetrics ACL injury-prevention programs, that have been shown to reduce the risk of knee injury in soccer players. 23 To address this public health concern, these programs should be conducted in local community soccer clubs and through regional and national youth soccer organizations as a valuable way to reduce time missed from competition because of injury. At the time of this writing, the US Youth Soccer Web site 12 discusses knee injuries and highlights the 11þ program from Fédération International de Football Association under the link ''Health and Safety Resources Center.''…”
Section: Discussionmentioning
confidence: 99%
“…41 The efficacy of prevention programs in decreasing the incidence of ACL tearing was sustained by the results of meta-analyses published by Hewett in 2010 20 , Yoo in 2010 36 , and Sadoghi in 2012. 42 There are several biomechanical and clinical studies and meta-analyses supporting the possibility of preventing ACL injury by using validated prevention training programs, but we need future research to determine the importance of neuromuscular imbalances and generate solutions to prevent non-contact ACL injuries. One significant difficulty in the implementation of prevention programs is compliance.…”
Section: Prevention Programsmentioning
confidence: 99%
“…Improved understanding of these biomechanical, anatomic, and kinematic risk factors of ACL injuries has led to the development of ACL injury prevention programs. These programs have components of neuromuscular, proprioceptive, and plyometric training targeted at minimizing impairments that may lead to injury and re-injury and have been shown to be effective in decreasing the rate of ACL injuries in high school, college, and professional players [77][78][79][80][81][82][83]. Over the last 3 years, several studies have investigated the utility of these prevention programs in young athletes.…”
Section: Risk Factors and Preventionmentioning
confidence: 99%